The role of iron deficiency and factors associated with anemia during pregnancy in Southeastern Tigray, Ethiopia, 2020 - Tedros Bereket; Freweini Gebrearegay Tela; Gebretsadkan Gebremedhin Gebretsadik; Selemawit Asfaw Beyene (PLoS ONE, 2025)
Background Pregnant women are more likely to experience anemia due to their increased need for nutrients, and anemia has been associated with unfavorable maternal-fetal outcomes. In Ethiopia, anemia rates are increasing despite efforts to reduce them. Besides, the extent to which iron deficiency contributes to anemia in this population is unclear. Therefore, this study aimed to assess the role of iron deficiency and factors associated with anemia during pregnancy in the southeastern zone of Tigray, Ethiopia. Method A facility-based, cross-sectional study was conducted among 311 pregnant women who attended four health facilities in the southeastern zone of Tigray region from January to June 2020. The study utilized a semi-structured, pretested questionnaire to collect data. The data were entered into Epi data 3.1 and analyzed using SPSS version 25. Candidate variables with a p-value ≤ 0.25 in the bivariate logistic regression were considered to the final model of multivariate logistic regression analysis. Adjusted odds ratio with a 95% confidence interval and a p-value of ≤ 0.05 were used to declare statistical significance for the factors associated with anemia. Results A total of 311 mothers had completed the survey with a response rate of 98.1%. The overall magnitude of anemia was 55(17.7%). Out of the anemic pregnant women, 30(54.5%) were due to iron deficiency. Third-trimester pregnancy (AOR = 4.9; 95% CI:1.49, 15.98), interpregnancy gap of ≤ 2 years (AOR = 7.7; 95% CI: 2.71, 21.64), coffee/tea intake immediately after meal (AOR = 3.0; 95% CI: 1.02, 8.92), low diet diversity score (AOR = 4.2; 95% CI: 1.02,17.57), not taking iron-folic acid supplementation (AOR = 2.6; 95% CI: 1.05, 6.70), and Mid upper arm circumference value of < 23cm (AOR = 2.7; 95% CI: 1.16, 6.47) were independent factors associated with anemia. Conclusion Based on the findings, anemia is a mild public health concern in the study areas. Additionally, over 50% of the anemia cases were attributed to iron deficiency anemia. Nutritional counseling on food diversification, especially the consumption of iron-rich foods, and delaying the drinking of coffee/tea after a meal, as well as iron-folic acid supplementation, are needed to reduce anemia in the study area.